แนวคิดและกลวิธีการเฉลิมพระเกียรติพระบาทสมเด็จพระปรมินทรมหาภูมิพลอดุลยเดชในทศชาติคำฉันท์ - ปัทมาภรณ์ ผ่องแผ้ว (คณะมนุษยศาสตร์ มหาวิทยาลัยเกษตรศาสตร์, 2022)
This article aims to study the concepts and techniques to eulogize King Rama IX which appear in Thotsachat Khamchan composed by Boontuen Sriworrapot. The study reveals the concepts of eulogizing King Rama IX as a Bodhisattrarajah, a great king, a father of Thai people, a universal monarch and Vishnu avatar. The important techniques employed to convey the eulogistic concepts are the use of royal duties and conducts of King Rama IX as the Bodhisattra characters, the excision of the event details from Jataka- Atthakhatha to emphasize the eulogy, the addition of the convention of thai verse literature, the use of the conversation of the characters and the creation of comparable dual character. This study shows the significance of Ten-Jataka on creating contemporary eulogistic literature.